Find the 15th term in the following sequence:
0 , 5 , 9 , 1 2 , 1 4 , 1 5 , 1 5 , 1 4 , . . .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
a n = 2 ( 1 − n ) ( n − 1 2 )
There is a second possible solution to this which leads to a second possible answer.
a n = a n − 1 + 6 − n
with base case a 0 = 0
Log in to reply
I think a 1 = 0 . You will get correct answer by this!
Trevor, you will get the same answer. Note that because your first term is a 0 , hence the fifteenth term is actually a 1 4 , which is equal to -21.
Both of your solutions describe a quadratic form for the answer. If they agree on 3 terms, then they must agree everywhere.
set X=5 start with adding X to each term and then set X=x-1
0+5 = 5, 5+4 = 9, 9+ 3= 12, 12+2= 14, 14+ 1= 15, 15+0 = 15, 15+(-1) = 14, 14+ (-2)= 12, . . . . -13+(-8)= -21
-21. after 15 it will gradually decrease , like 1>2>3....
Problem Loading...
Note Loading...
Set Loading...
Original Sequence: 0, 5, 9, 12, 14, 15, 15, 14, ...
Find the differences between each term: +5, +4, +3, +2, +1, 0, -1 Find the second differences. -1, -1 ,-1, ... Half the second difference and multiply it by n^2. -1/2n^2
Make a new sequence using -1/2n^2. -0.5, -2, -4.5, -8. -12.5, Subtract the new sequence from the original sequence to find the differences. 0.5, 7, 13.5, 20, 26.5 Find the second differences. 6.5, 6.5, 6.5, ... The sequence 6.5n - 6 must be added to the new sequence to get the original sequence.
Hence the nth term sequence is -0.5n^2 +6.5n-6 .
Substitute 15 as n. -0.5(15^2)+6.5(15)-6 = -21
The answer is -21.